New records of Holochilus chacarius (Rodentia, Cricetidae) in the Carcarañá river basin (Santa Fé province, Argentina) and biogeographical considerations - Rimoldi, Pablo G. (2021)
The collection and analysis of pellets is an adequate method in the study of small prey, because it allows the study of large areas, generates a large number and variety of individuals per lot. The order Strigiformes has the largest number of studies on the diet of birds of prey worldwide, highlighting those referring to Tyto furcata with a large number of contributions on the analysis of its regurgitates. The study of the regurgitations of this species has helped to make new interpretations about the distribution, taxonomy, and conservation of many species of rodents. Here, the presence of Holochilus chacarius is described in the south of the province of Santa Fe from the collection and analysis of pellets of the Barn Owl (Tyto furcata). These records expand the distribution of H. chacarius in the province and contribute to updating the existing distribution maps.